The Implementation of Clarisketch Learning Media in Speaking Skills: (A Quasi-Experimental Research in the First Grade of SMPN 1 Pandeglang) - Sonia Oktaviani; As'ari As'ari; Eulis Rahmawati (English Education, Linguistics, and Literature Journal, 2023)
This research aims to investigate the effect of using Clarisketch learning media on speaking skills in the first grade of SMPN 1 Pandeglang. The purpose of the study were 1) To know the students’ ability speaking skills; and 2) To know the effect of using Clarisketch learning media on speaking skills. This study used a quasi-experimental study involving two classes as the sample. Moreover, the research design of this study consists of pre-test, treatment, and post-test where VII C class acts as experimental class and VII D class acts as control class. To fulfill the purpose of this research, the researcher took 60 students in first grade as respondents. Then they were divided into two groups, experimental and control. In the process of treatment, the experimental group received Clarisketch as learning media, while the control group received the conventional teaching. Based on the calculation by using t-test, this study showed that = 18,11 is higher than = 2,39, in the degree of significance 1% = 2,39, and in the degree of significance 5%= 1,67. Despite students' scores increasing and based on the process and result giving a significant effect, the average score of the experimental class does not reach the minimum completeness criteria for English Subjects in the 2013 curriculum is 77. it means that it was not effective use in speaking skills in the first grade of SMPN 1 Pandeglang because of other factors.